Historicizing online politics : telegraphy, the Internet, and political participation in China - Zhou, Yongming, 1963- (Stanford University Press, 2006)
It is widely recognized that internet technology has had a profound effect on political participation in China, but this new use of technology is not unprecedented in Chinese history. This is a pioneering work that systematically describes and analyzes the manner in which the Chinese used telegraphy during the late Qing, and the internet in the contemporary period, to participate in politics. Drawing upon insights from the fields of anthropology, history, political science, and media studies, this book historicizes the internet in China and may change the direction of the emergent field of Chinese internet studies. In contrast to previous works, this book is unprecedented in its perspective, in the depth of information and understanding, in the conclusions it reaches, and in its methodology. Written in a clear and engaging style, this book is accessible to a broad audience.